Estimating the metabolic rate and associated physiological response for Indian subjects through climate chamber experiments - Anand, Vivek; Sendhil, Devi; Rajasekar, E. (Building and environment, 2022)
This paper estimates metabolic rate and physiological response associated with different activity intensities through controlled climate chamber experiments. We investigate the effect of activity intensity, personal and environmental factors on the subjects' heart rate, oxygen consumption, energy expenditure, and metabolic rate (Mr). Forty-eight adult Indian subjects categorized based on age, gender, Body Mass Index (BMI), ethnicity and dietary practices are subjected to different temperature, relative humidity, and air velocity set-points. Cardio-Pulmonary Exercise Test (CPET) and Resting Metabolic Rate (RMR) Test are performed in a climate camber based on appropriate experimental protocols. We find substantial variation in the physiological responses concerning activity intensity. The difference in Mr for different age and BMI groups is statistically significant. Mr of stationary activities exhibits marginal variation with temperature change. However, Mr of non-stationary activities shows significant variation with temperature variations. The effect of relative humidity on Mr is significant for non-stationary activities. Ethnicity and dietary habits of the subjects depict good relationship with the mean Mr for non-stationary activities. There is a significant difference observed in the metabolic stabilisation period for different age group categories in non-stationary activities. We present the impact of these intrinsic variations of Mr on thermal comfort estimations. •Metabolic rate and physiological response for different activities are assessed for Indian subjects in a climate chamber.•A significant difference is found in metabolic rate and physiological response for different age, gender and BMI groups.•There is a significant difference in the metabolic rate of subjects of different ethnicity and dietary habits.